Fact and Taste - Tomaiuolo, Saverio (English Literature, 2015)
Hard Times is an example of Dickens’s desire to create a narrative hybrid, composed – as it is – of different literary genres. Thomas Gradgrind and Mr. Sleary’s use of language as an expression of their frame of mind (in Mikhail Bakhtin’s terminology, their “ideologeme”) embodies their adherence to textual and ideological norms (the “facts”) or their infraction (“People mutht be amuthed”). Nevertheless, the “carnevalesque” nature of the circus, which epitomises the transgression of social and cultural norms, is not to be intended as a negation of those social and family principles that Dickens’s novel advocates against disruptive utilitarian politics. In his view, it is through their (apparent) negation that traditional Victorian values may be affirmed and consolidated thanks to a mutual form of cultural “infection”. At the same time, Hard Times dramatizes, in a metaliterary twist, Dickens’s defence of the role of the writer, and of the artist, as a “social educator” in the figure of Sleary, who positively contaminates Thomas Gradgrind’s “pure” factual approach.